Analisis Kemampuan Koneksi Matematis Ditinjau dari Self-Concept Siswa - Ade Yuliani; Reza Muhamad Zaenal (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the description of the ability of mathematical connections in terms of students' self-concept. It is important to know the description of the level of mathematical connection ability possessed by students so that it can be used as a reference in planning the right learning process. Self-concept is used to determine the description mathematical connection abilities, where self-concept as an affective aspect plays an important role in the cognitive aspects of students. This research is descriptive qualitative research with 53 students of class VIII SMP Negeri 1 Kramatmulya as participants who were determined by purposive sampling. Participants were given a mathematical connection ability test and a self-concept questionnaire. Furthermore, interviews were conducted with several positive self-concept and negative self-concept participants who obtained the highest and lowest questionnaire scores from each self-concept. The data obtained was analyzed using analysis model Miles and Huberman which is divided into three stages, namely data reduction, data display, and conclusion. The results showed that students with positive self-concepts had all indicators of mathematical connection ability. Then students with negative self-concept are less able to use and master the indicators of mathematical connection ability. This is because most of the indicators of mathematical connection ability are still not mastered by students in solving the problems given